'Those of the Circumcision' (Gal 2:12) Meaning, Reference and Origin - Reuter, Rainer (Filología neotestamentaria, 2009)
According to a certain lexicographical consensus the phrase oi ek peritomes is interpreted either as meaning Jewish Christians or simply Jews. A closer observation of the verses shows that in all cases oi ek peritomes means 'circumcised people,' 'Jews'. When New Testament authors refer to Christian Jews it is always indicated by special reference markers in the context. The same is the case in Gal 2:12. While the meaning of oi ek peritomes is Jews, the reference demanded by the context are James-people as Christian Jews. Moreover, Paul used this particular phrase because of its special semantic extension. In the Pauline corpus constructions with oi ek … either mean the social or ethnic origins of a person or a basic theological orientation. The latter meaning fits best in Gal 2:12 because the following context shows a strong contrast between oi ek pisteos and osoi ... ex ergon nomou and its synonym oi ek peritomes. Therefore oi ek peritomes in Gal 2:12 means Jews, refers to the James-people and characterises them as zealous observers of Torah.